Effect Of Variation In Liquefied Petroleum Gas (LPG) Proportions In Spark Ignition Engine Emissions. - Mustafa, K F; H W, Gitano-Briggs (2008)

(untitled)
This paper presents an experimental investigation of a Liquefied Petroleum Gas (LPG) fueled four-stroke spark ignition engine. The primary objective of the study was to determine and quantify the exhaust emissions from the engine.